2003
DOI: 10.1038/sj.onc.1206603
|View full text |Cite
|
Sign up to set email alerts
|

Lats2, a putative tumor suppressor, inhibits G1/S transition

Abstract: Lats2 is a new member of the Lats tumor suppressor family. The human LATS2 gene is located at chromosome 13q11-12, which has been shown to be a hot spot (67%) for LOH in nonsmall cell lung cancer. In order to understand the function of LATS2 in the control of tumor development, we ectopically expressed mouse Lats2 via retroviral infection in NIH3T3/v-ras cells to examine whether Lats2 plays a role in suppressing tumor development and regulating cell proliferation. We have found that ectopic expression of Lats2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
174
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(183 citation statements)
references
References 29 publications
7
174
1
1
Order By: Relevance
“…In contrast, LATS2 (the second human counterpart of Drosophila Lats) seems to function in more than one cell cycle stage. On one hand, it was reported that LATS2 overexpression inhibits G1/S transition [90]. On the other hand, LATS2 overexpression can also lead to a G2/M cell cycle arrest [91].…”
Section: Mammalian Hippo Signalling In the G2/m Phase Of The Cell Cyclementioning
confidence: 99%
“…In contrast, LATS2 (the second human counterpart of Drosophila Lats) seems to function in more than one cell cycle stage. On one hand, it was reported that LATS2 overexpression inhibits G1/S transition [90]. On the other hand, LATS2 overexpression can also lead to a G2/M cell cycle arrest [91].…”
Section: Mammalian Hippo Signalling In the G2/m Phase Of The Cell Cyclementioning
confidence: 99%
“…Over-expression of LATS1 also up-regulates the proapoptotic protein BAX in human mammary tumor cells and the activity of caspase-3 in human colorectal tumor cells to induce apoptosis [24,25]. Meanwhile, LATS2 has been demonstrated to regulate cell growth by inducing cell cycle arrest at the G 1 /S phase through the disruption of the CDK2/Cyclin E complex or at the G 2 /M phase by inhibiting Cdc2 kinase activity, by an as yet unknown mechanism [27,28]. Moreover, LATS2-deficient MEFs (Mouse Embryonic Fibroblasts) exhibit defects in growth control and centrosome duplication, which results in misalignment of chromosomes and failure of cytokinesis [23].…”
Section: Large Tumor Suppressor (Lats)/nuclear Dbf2-related (Ndr) Genmentioning
confidence: 99%
“…The LATS/NDR protein kinase family has been implicated in many cellular processes and LATS1/2 has been shown to suppress tumor growth [23,24,25,27,30,32]. …”
Section: Effect Of Hmob1a/1b On Cell Proliferationmentioning
confidence: 99%
“…34 Beside their roles within the Hippo pathway, Lats1/2 may regulate cell cycle progression and apoptosis. [35][36][37][38] Lats1 has been shown to regulate both mitotic exit 39 and cytokinesis 40 and to play a role in cellular senescence, since reduction of Lats1 levels is, at least partly, responsible for cytokinetic block in senescent cells. 41 Lats2 has also been found to protect p53 from Mdm2-mediated degradation while p53 stimulates Lats2 expression.…”
Section: Mst1/2mentioning
confidence: 99%
“…49 In vitro, overexpression of Lats1 or Lats2 is sufficient to suppress ephithelial-messenchymal transition and tumor growth of cancer cells while their downregulation result in cell overgrowth and transformation. 32,35,36,44,45,50 …”
Section: Mst1/2mentioning
confidence: 99%